STRATEGI KEPEMIMPINAN KEPALA SEKOLAH MENUJU SEKOLAH UNGGUL - Wachidah Yuliana Taryanti; Puspa Djuwita (Manajer Pendididikan, 2019)
Abstrack: the purpose of this study was to describe the Strategie of school Pincipale Leadership toward Excellent School in Elementary school 109 Bengkulu Utara. The Method used in this study was descriptive qualitative with research subjects are the school principal, the vice of the school principal,the teacher and the staff. The dates are collected by using interview. Observation and documentation and analyzed with qualitative technique.the result of this study  shows: 1) The strategic of school principles leadership in developin school vision,mission were made by desaing shorter strategic ( estimated 5 years), longterm strategic 915 years), 2). The strategic of school principles in develovin curriculum was made by (a). change education system, (b). change the school curriculum, (c). giving in- service education & staf development, (d). reorganize school ( experiment & research). 3). The strategic of school leaderhip principle in developin students was made by in creasing digital ability,extraculiculer activity & sport. 4). The strategic of school leadersip in developin infrastructure with the provision of sports fields, computer classes and libraries.Keywords: School Principal's , Leadership Strategy, Excellent School.